2014
DOI: 10.1074/jbc.m114.602938
|View full text |Cite
|
Sign up to set email alerts
|

Leigh Syndrome in Drosophila melanogaster

Abstract: Background: Mutations in SURF1, a human gene important for the assembly of cytochrome-c-oxidase (COX) causes Leigh Syndrome, a mitochondrial encephalopathy.Results: Knockdown of Surf1 in Drosophila matches the biochemical features of the human disease.Conclusion: In Drosophila SURF1 is essential to maintain mitochondrial function and its silencing leads to COX deficiency.Significance: Drosophila offers new tools to investigate the pathogenic mechanism of Leigh Syndrome.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
12
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 23 publications
(12 citation statements)
references
References 61 publications
0
12
0
Order By: Relevance
“…, those linked to the neuron- and muscle-specific elav and Mhc promoters, respectively ( Osterwalder et al 2001 ), or for specific expression in other tissues such as the fat body ( Roman et al 2001 ). Subsequently, the “ubiquitous” GS drivers (such as tubGS and Actin5C-GS ) have been brought into use for inducing broad expression, both in adults and larvae ( Ford et al 2007 ; Waskar et al 2009 ; Wigby et al 2011 ; Paik et al 2012 ; Kuo et al 2012 ; Kemppainen et al 2014a , b ; Sun et al 2014 ; Da-Rè et al 2014 ).…”
Section: Discussionmentioning
confidence: 99%
“…, those linked to the neuron- and muscle-specific elav and Mhc promoters, respectively ( Osterwalder et al 2001 ), or for specific expression in other tissues such as the fat body ( Roman et al 2001 ). Subsequently, the “ubiquitous” GS drivers (such as tubGS and Actin5C-GS ) have been brought into use for inducing broad expression, both in adults and larvae ( Ford et al 2007 ; Waskar et al 2009 ; Wigby et al 2011 ; Paik et al 2012 ; Kuo et al 2012 ; Kemppainen et al 2014a , b ; Sun et al 2014 ; Da-Rè et al 2014 ).…”
Section: Discussionmentioning
confidence: 99%
“…Based on additional genetic and biochemical data, Zhang et al, concluded that Sicily acts as a co-chaperone for Hsp90 to stabilize Complex I proteins prior to their entry into the mitochondria. Together with insights obtained from other fly genes whose human orthologs are also linked to Leigh syndrome such as ND-42 (Burman et al, 2014) and Surf1 (human ortholog: SURF1, Da-Rè et al, 2014), we now have a better understanding of this disorder at the molecular, cellular and organismal level.…”
Section: Mitochondrial Dysfunction Oxidative Stress and Lipid Droplementioning
confidence: 99%
“…In a LS Drosophila model, the constitutive SURF1 knockdown is lethal in larvae that however display defects in all complexes of the mitochondrial respiratory chain (MRC) and impaired muscular development. In a conditional central nervous system (CNS)-restricted Drosophila model the knockdown of SURF1 leads to isolated COX deficiency in adult flies [ 17 ]. The failure of small animal models, in particular rodents, to mimic the main features of the human syndrome prompted us to generate a large animal model [ 18 ].…”
Section: Introductionmentioning
confidence: 99%